Pentingnya Vitamin A Untuk Ibu Menyusui serta Pembuatan Sosis Wortel di Desa Suka Maju Kabupaten Muaro Jambi - Herinawati Herinawati; Lia Artika Sari; Atika Atika; Iksaruddin Iksaruddin (Sekolah Tinggi Ilmu Kesehatan Baiturrahim Jambi, 2021)
19 million pregnant women are thought to have vitamin A deficiency. Vitamin A deficiency during pregnancy and postpartum can seriously affect the health of the mother and baby. Vitamin A supplementation is sometimes recommended. Although the health consequences of Vitamin A deficiency (VAC) are not well defined, recent data suggest that VAD in women of reproductive age can increase the risk of morbidity and mortality during pregnancy and the early postpartum period. Severe VAC in the mother also poses a loss for newborns because it can result in an increase in mortality in the first month of life. The results showed that Vitamin A deficiency (VAC) is also associated with high morbidity and mortality rates, especially among toddlers. Every year it is estimated that more than 60,000 Indonesian children suffer from severe visual impairment and one third of them become blind which cannot be cured. This is because the consumption of vegetables is still low, including carrots. This community service activity aims to increase the knowledge, attitudes and behavior of the community about the importance of Vitamin A for postpartum and breastfeeding mothers as well as making carrot sausage in Suka Maju Village, RT.09 Mestong District, Muaro Jambi Regency. The target of this service is breastfeeding mothers and posyandu volunteers. This activity is carried out from February to May. Participants who took part in the activities of postpartum mothers and posyandu volunteers, located at the Village Midwife's House RT 09, Mestong District, Muaro Jambi Regency. It is recommended to the puskesmas, village heads to be able to socialize and apply in promoting the processing of foods containing vitamin A in their daily diet